Analisa Perubahan Aliran Pada Model SPAR (4VP) - Nurhikma Nurhikma; Fuad Mahfud Assidiq (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
Research on the flow around the SPAR model was carried out with the aim of finding out how much effect the flow has on the SPAR structure used in offshore wind turbines. SPAR is a type of floating structure that can usually be used in deep seas and is an effective and reliable structure in terms of construction. Spar has the advantage that the buoyancy point (KB) is above the gravity point (KG), thus providing good stability. However, there are still obstacles to the use of SPAR structures in the deep sea, especially when environmental conditions are extreme, where SPAR structures are not able to reduce currents at a certain speed level. Then, this research aims to test the SPAR model with a four vertical plate (4VP) configuration system which is then modeled using Computational Fluid Dynamics (CFD) based numerical modeling which aims to investigate the flow around the SPAR in terms of flow velocity. Especially at certain flow velocity levels, the velocity is chosen carefully at each level starting from: V1 = 0.611m/s, V2 = 6.114, V3 = 61.144, V4 = 611.438. The addition of vertical plates to the bottom construction of the SPAR has a role in dampening the flow and also turbulent effects due to current impacts.